Content development, accessibility and feasibility of a self‐report tool for use in programmes serving youth with cognitive disabilities: The Participatory Experience Survey. (11th February 2019) - Liljenquist, Kendra; Kramer, Jessica; Rossetti, Zachary; Coster, Wendy
Abstract : Introduction: Participation in community‐based recreation and leisure activities may afford valuable opportunities to young people with cognitive disabilities (CD) to develop important self‐determination skills needed for success in adulthood. To evaluate whether these programmes are achieving their intended impact, it is important to have a tool that captures the perspective of the participants using an accessible method. This article describes the content development and evaluation of accessibility and feasibility of the Participatory Experience Survey (PES). Method: Participant observation and focus group sessions were conducted in conjunction with a summer youth programme hosted by a special education advocacy organisation. Photos were used to guide identification of factors influencing both negative and positive experiences. Findings informed question content. Three groups of stakeholders, parents of youth with CD (Group 1), service providers (Group 2), and experts in cognitive disability and/or programme planning (Group 3) reviewed the PES to provide feedback on the relevance and accessibility of the measure. After stakeholder feedback was incorporated, cognitive interviewing was conducted with young people with CD to assess instrument accessibility and appropriateness for use in context. Results: Youth described their participation in three categories: personal, social and environmental. Stakeholder Groups 1 and 2 identified 15 questions as needing revisions. Seven additional questions were added based on suggestions from stakeholder Group 3. Cognitive interviewing led to revision of 13 questions and removal of 16 questions due to issues related to vocabulary, item meaning, response bias, repetitiveness and length. Conclusion: The PES has the potential to offer programmes a means to more fully include young people with disabilities in programme evaluations, leading to better‐structured, more supportive programmes. Additional validity and feasibility work is needed to confirm these initial findings.